Studies of the molecules form plasmodium falciparum that mediate pathogenesis - Mo, Min (2008)
Adhesion of erythrocytes infected by Plasmodium falciparum to receptors of the microvasculature is a major contributor of parasite pathology and morbidity. It is mediated by the P. falciparum erythrocyte membrane protein 1 (PfEMP-1) which is expressed at the surface of infected erythocytes and is linked to both antigenic variation and cytoadherence. The PfEMP-1 protein contains multiple adhesive modules, including the cysteine-rich interdomain region (CIDR). The interaction between CIDRa and CD36 promotes stable adherence of parasitized erythrocytes to endothelial cells. Here we show that a segment within the C-terminal region of CIDRa determines CD36 binding specificity. Antibodies raised against this segment can specifically block the adhesion of various parasite stains to CD36. Thus, small regions of PfEMP-1 that determine binding specificity could form suitable components of an anti-sequestration malaria vaccine effective against different parasite strains.